Detection of Ehrlichia platys DNA in Brown Dog Ticks (Rhipicephalus sanguineus) in Okinawa Island, Japan - Inokuma, Hisashi (American Society for Microbiology, 2000)
Thirty-two Rhipicephalus sanguineus females collected from eight free-roaming dogs in Okinawa Island, Japan, were examined for ehrlichial DNA by 16S rRNA-based PCR and subsequent sequencing. Partial sequences of Ehrlichia platys 16S rRNA (678 to 679 bp) were detected in three ticks (9.4%) from two dogs. This is the first report of detection of E. platys in Japan, and also the first report of detection in ticks.